Work Meetings as the Main Pillar of Management and Formation of Youth Social Character in Karang Taruna Organizations - Nurhikmah; Ibrahim, Muhammad (Jurnal Al Maesarah, 2025)
This research examines how work meetings serve as the primary foundation for managing and developing social character within Karang Tarun Boto Lempangang's youth groups. The effectiveness of work meetings in enhancing coordination, communication, and decision-making inside the youth organization is the primary issue raised. Due to few studies that specifically reviewed the role of work meetings in influencing the management of social organizations such as Karang Taruna, this research was conducted. The main respondents were members and administrators of Karang Taruna who actively participated in work meetings. Data analysis was carried out using thematic analysis techniques to identify the main themes related to the role of work meetings. According to the study's findings, productive meetings can speed up decision-making, enhance internal communication, and enhance member coordination. Work meetings also contribute to members' empowerment and increase sense of community inside the company. The study's conclusion is that in order to properly accomplish organizational objectives, Karang Taruna management must improve the quality of work meetings.